2002
DOI: 10.1590/s1517-74912002000400002
|View full text |Cite
|
Sign up to set email alerts
|

Growth of cell populations of the intralobular duct in the submandibular gland of the mouse during postnatal development

Abstract: The growth of cell populations of intercalated ducts (ID), striated ducts (SD) and convoluted granular tubules (CGT) of the submandibular gland of the mouse was analyzed, during the period of 14 to 84 days of postnatal life, by means of morphometric methods. The absolute number of cells in each type of duct was submitted to curve fitting by means of linear regression analysis, and the obtained equations were: y = 13.22 + 0.87x for ID cells in the growth period of 14 to 84 days; y = -18.82 + 3.69x and y = 176.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Nuclei of proliferating cells in the late G1 phase to the S phase, G2 phase, and M phase of the cell cycle therefore stain positive to anti-PCNA immunohistochemical staining, which is thus capable of detecting cellular proliferative potential. The proliferative activity of cells that compose the salivary glands reportedly changes with gland development (Chang and Barka, 1974, Redman, 1995, Taga and Sesso, 1998, Taga and Sesso, 2001, Taga and Pardini, 2002. Taga et al (1998) found that with respect to the cellular proliferative potential of rat sublingual glands, proliferation of serous and mucous acinar cells peaked on day 5 after birth and gradually declined thereafter, with a slight increase in proliferation on day 20 followed by another decline.…”
Section: Detection Of Cellular Proliferative Activity and Measurementmentioning
confidence: 99%
“…Nuclei of proliferating cells in the late G1 phase to the S phase, G2 phase, and M phase of the cell cycle therefore stain positive to anti-PCNA immunohistochemical staining, which is thus capable of detecting cellular proliferative potential. The proliferative activity of cells that compose the salivary glands reportedly changes with gland development (Chang and Barka, 1974, Redman, 1995, Taga and Sesso, 1998, Taga and Sesso, 2001, Taga and Pardini, 2002. Taga et al (1998) found that with respect to the cellular proliferative potential of rat sublingual glands, proliferation of serous and mucous acinar cells peaked on day 5 after birth and gradually declined thereafter, with a slight increase in proliferation on day 20 followed by another decline.…”
Section: Detection Of Cellular Proliferative Activity and Measurementmentioning
confidence: 99%